KAJIAN LITERATUR: PENGARUH TATA KELOLA PERUSAHAAN PADA PERFORMA KEUANGAN - Siswanto, Felicia; Kertanegara, I Wayan Alvin; Kevin, Kevin; Ningsih, Rahayu; Meiden, Carmel (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
The purpose of the study was to identify the elements that affect corporate governance. Corporate governance is a picture of the relationship between parties that influences the direction of the company and financial performance. Basically, to find out how much influence corporate governance has on a company's financial performance requires the application of agency theory. This research uses a method of literature studies that studies and examines documents related to corporate governance especially about the influence of corporate governance on financial performance. The data used in this study is secondary data. The implementation of corporate governance should have a positive impact on the performance of the company, but in reality there are still many companies that have not implemented good corporate governance, because most companies only carry out government rules without deepening the role and function of corporate governance itself.